The prevalence of Coxiella burnetii shedding in dairy goats at the time of parturition in an endemically infected enterprise and associated milk yield losses - Canevari, Jose Tobias; Firestone, Simon M.; Vincent, Gemma; Campbell, Angus; Tan, Tabita; Muleme, Michael; Cameron, Alexander W. N.; Stevenson, Mark A. (Springer Nature, 2018)
Background: This was a panel study of the prevalence of C. burnetii infection in does in an endemic dairy goat enterprise in Victoria, Australia. Our first objective was to determine the prevalence of does shedding C. burnetii at the time of parturition and to quantify the concentration of genome equivalents (GE) present in each C. burnetii positive sample. Our second objective was to determine the proportion of positive does that were persistent shedders. Our final objective was to quantify the association between C. burnetii qPCR status at the time of kidding and daily milk volumes produced during the subsequent lactation. Results: Vaginal swabs (n= 490) were collected from does at the time of kidding and analysed using a quantitative polymerase chain reaction (qPCR) assay. Shedding of C. burnetii was detected in 15% (95% CI: 12% to 18%) of the sampled does. Does were classified as qPCR-negative, qPCR-positive low and qPCR-positive high based on the estimated concentration of GE from the qPCR. Persistent shedding at relatively low concentrations was detected in 20% (95% CI: 10% to35%) of shedding does sampled again at their subsequent parturition. After controlling for possible confounders and adjusting for variation in daily milk yields at the individual doe level, daily milk yields for qPCR-positive high does were reduced by 17% (95% CI: 3% to 32%) compared to qPCR-negative does (p= 0.02). Conclusions: Shedding concentrations of C. burnetii were highly skewed, with a relatively small group of does shedding relatively high quantities of C. burnetii. Further, high shedding does had reduced milk yields compared to qPCR-negative does. Early detection and culling of high shedding does would result in increased farm profitability and reduce the risk of Q fever transmission.